NIKAH MISYAR DALAM PERSPEKTIF MAQASHID SYARIAH: STUDI YURIDIS TERHADAP FENOMENA KEKINIAN DI BANDA ACEH - Ali Furqan Ali Furqan; Zahrul Fatahillah; Uswatun Hasanah (Sekolah Tinggi Ilmu Syari'ah (STIS) Nahdlatul Ulama Aceh, 2025)
Marriage in Islam is a sacred institution that serves to uphold moral values and social stability, but the emergence of misyar marriage has sparked controversy because the wife relinquishes some of her rights. This phenomenon began in Banda Aceh and has raised legal and social issues. This study examines the views of contemporary scholars on misyar marriage within the framework of maqashid syariah. The primary focus is on the compatibility of this practice with the principle of protecting the rights of women and children. Additionally, the study discusses how Indonesian family law responds to this phenomenon. The research employs a normative approach, using it to thoroughly examine Islamic texts such as the Quran, hadith, and fiqh books that discuss marriage, particularly the form of misyar marriage, and to analyze them using the applicable legal norms. The results of the study show that although misyar marriage is considered valid in fiqh by some scholars, this practice remains controversial because it has the potential to weaken the protection of women and children. The approach that emphasizes formal validity often ignores moral responsibility in fostering a harmonious family. In the context of maqashid syariah, misyar marriage is considered to not fulfill the objectives of preserving offspring and justice. In Banda Aceh, this practice contradicts the values of customary law and protection norms in national law. When women relinquish their rights, the risks of inequality and social harm increase. Therefore, a more contextual and integrative approach to Islamic family law is needed. This approach must combine the values of maqashid, the principle of justice, and legal protection to ensure that marriage remains meaningful both spiritually and socially. The relevance of Islamic law must be maintained to ensure it continues to provide tangible benefits for communities that uphold justice and the common good.